Continuous Flow Synthesis of Anticancer Drugs - Mara Di Filippo (MDPI AG, 2021)
Continuous flow chemistry is by now an established and valued synthesis technology regularly exploited in academic and industrial laboratories to bring about the improved preparation of a variety of molecular structures. Benefits such as better heat and mass transfer, improved process control and safety, a small equipment footprint, as well as the ability to integrate in-line analysis and purification tools into telescoped sequences are often cited when comparing flow to analogous batch processes. In this short review, the latest developments regarding the exploitation of continuous flow protocols towards the synthesis of anticancer drugs are evaluated. Our efforts focus predominately on the period of 2016–2021 and highlight key case studies where either the final active pharmaceutical ingredient (API) or its building blocks were produced continuously. It is hoped that this manuscript will serve as a useful synopsis showcasing the impact of continuous flow chemistry towards the generation of important anticancer drugs.